PENGEMBANGAN MEDIA PEMBELEJARAN BERBASIS GENIALY UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS VIII MATA PELAJARAN PAI MATERI MINUMAN KERAS - M. Zhunai Idi Nur; Jasiah Jasiah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2026)
This study aims to develop Genially-based learning media to strengthen Islamic Religious Education (PAI) instruction on the topic of the dangers of alcoholic beverages, responding to the need for more interactive digital media innovation in Islamic education at the junior high school (SMP) level. The research problem is grounded in the continued dominance of lecture-based delivery and linear slide presentations in PAI learning, resulting in limited adoption of interactive media formats to deliver normative content such as khamr (forbidden intoxicants) prevention in ways that stimulate learner attention, exploration, and engagement. The study applies a simplified Research and Development (R&D) approach, covering the stages of planning, development, and expert validation carried out within a university classroom environment, as its priority is to produce an initial media design prototype and ensure conceptual and interface feasibility prior to future user-based trials involving teachers and students in schools. The learning media product design incorporates a structured home page, organized navigation buttons, visually enriched material pages explaining the negative impacts of alcoholic beverages, embedded educational videos, and learning quizzes integrated through external game-based assessment models in Wordwall. Media evaluation is conducted through classroom presentations assessed by the academic supervisor, whose feedback targets improvements to layout neatness and design consistency, without reviewing the accuracy of the learning substance. The media development results indicate strong preliminary feasibility regarding learning flow structure, interface appeal, navigation clarity, and interactive element integration, alongside recommended technical revisions to layout arrangement and visual consistency to achieve more coherent design delivery. The research concludes that Genially-based learning media holds significant potential as an innovative bridge for delivering Islamic moral values more visually and interactively, and provides suggestions for refinement including interface restructuring for improved neatness, quiz optimization for reduced reliance on external linking, and school-based collaborative testing with teachers and students in the next R&D stages.